Asuhan Keperawatan Gerontik Pada Tn. N Dengan Hipertens - Hisbul Habib, Habib; Ramaita; Dewi, Sandra; Yuderna, Vivi (Jurnal Keperawatan Medika, 2025)
Hypertension is a chronic disease that is often found in the elderly and is the main cause of serious complications such as stroke and heart failure. Based on data from the Sabai Nan Aluih Sicincin Padang Pariaman Regency Social Home (PSTW), hypertension is one of the seven most common diseases, with a prevalence of 13 cases in 2022, decreasing to 7 cases in 2024. This study aims to provide a comprehensive picture of geriatric nursing care for the elderly with hypertension. The study was conducted at the Sabai Nan Aluih Sicincin PSTW, Regency Padang Pariaman Regency, in 23 May 2025. The method used was a case study with a nursing care approach that included assessment, diagnosis, intervention, implementation, and evaluation. The results showed that the elderly who received directed nursing care experienced improvements in blood pressure management, reduced symptoms such as headaches and insomnia, and increased understanding of the disease and its treatment. The evaluation showed an increase in compliance in taking medication and diet management. In conclusion, the provision of continuous nursing care and appropriate education play an important role in controlling hypertension in the elderly in social care. This study contributes to geriatric nursing practice in an effort to improve the quality of life of the elderly with hypertension.